Effectiveness of Earthworm (Lumbricus rubellus Hoffmeister) and Cinnamon (Cinnamomum burmannii (Nees and T. Nees) Blume) Combination Capsule as Herbal Preparation in Reducing Cholesterol and Blood Sugar Levels - Erviani, Andi Evi; Hasyim, Zohra; Musdalifah; Asminah, Miska (Bogor Agricultural University, Indonesia, 2025)
Cardiovascular diseases, including coronary heart disease and heart attack symptoms, are the leading causes of death worldwide. High cholesterol levels and blood sugar levels contribute significantly to these diseases. Therefore, this study aimed to determine the effectiveness of combining capsules of earthworm (Lumbricus rubellus) and cinnamon (Cinnamomum burmannii) in lowering cholesterol and blood sugar levels. After conducting pre-clinical trials, clinical trials were further carried out in humans. Cholesterol and blood sugar levels were measured for 14 days in Phases 1 and 2. Statistical data analysis was conducted using the Shapiro-Wilk normality test, paired t-hypothesis test, Wilcoxon test, and frequency analysis. The results showed that in Phase 1, there were significant differences in volunteers' cholesterol and blood sugar levels with no clinical symptoms. The most significant decrease in cholesterol levels in female volunteers occurred at the age of 21-30 years, at 25.56%, while the most significant reduction in blood sugar levels occurred at 41-50 years, at 41.50%. On the other hand, the most significant decrease in cholesterol levels in male volunteers occurred at the age of 41-50 years at 33.08%, and the most significant reduction in blood sugar levels occurred at the age of >60 years at 38.87%. The most significant content in the combination capsule was fatty acids and cinnamaldehyde. In conclusion, consuming a combination of earthworm and cinnamon capsules for 14 days caused a reduction in cholesterol and blood sugar levels.